Non-affinity platform for processing knob-into-hole bispecific antibody - Xiaoyang Wang; Min Li; Mengting Li; Huoyan Hong; Kai Gao; Puya Zhao (Bioresources and Bioprocessing)
Abstract Bispecific antibodies hold significant potential as next-generation biotherapeutics owing to their ability to simultaneously bind to two targets. However, the development of bispecific antibodies as biotherapeutics has been hindered by the high levels of byproducts produced, including both high molecular weight and low molecular weight variants. In addition, the inevitable expression of homodimers in host cells presents further obstacles to the commercial development of bispecific antibodies as therapeutics. These byproducts, which share similar physicochemical properties with the target, pose several challenges for downstream purification processes. In this study, we present a non-protein A purification platform that employ a one-step polishing chromatography to purify bispecific antibodies. Mixed-mode Capto adhere resin was used to capture the target protein at pH 7.90 ± 0.10, followed by anion exchange chromatography as a polishing step. Overall, the results of this two-step chromatography purification method demonstrated at final product purity of 98% as assessed by size-exclusion high-performance liquid chromatography (SEC-HPLC) and 98% by reversed-phase-high-performance liquid chromatography (RP-HPLC), with residual host cell proteins controlled at 10 ppm and an excellent recovery rate of approximately 60%. This study presents a non-protein A capture platform, offering a simplified, streamlined, and competitive alternative to conventional affinity chromatography. Graphical Abstract